Low-frequency polarized electric field promotes stilbene biosynthesis by redirecting phenylpropanoid flux in postharvest grapes - Jie Zhu; Huangqiao Tao; Shi Chen; Linyu Nian; Mengjun Wang; Fei Li; Xu Lu; Chongjiang Cao (Food Chemistry, 2026)

Direct upcycling spent LiCoO2 into self-supporting cathodes via cobalt-seed induced slurry electrolysis - Yunhui Han; Xiangfei Zeng; Dejun He; Jiqin Wang; Kun Li; Qian Liang; Ling Hu; Anlong Han; Hao Li; Mengjun Chen (Chemical Engineering Journal, 2026)

Improving real-time PPP time transfer with the augmentation of predicted tropospheric products - Wei Xie; Kan Wang; Mengyuan Li; Zi Chen; Guolin Liu; Mengjun Wu; Xiaolong Mi; Xuhai Yang (GPS Solutions, 2026)
Real-time precise point positioning (PPP) time transfer is a crucial technique for the time and frequency field. However, its performance remains limited by the relatively long convergence time resulting from unstable parameter estimation in the initial stage. In this contribution, predicted tropospheric products provided by the Global Forecast System (GFS) are employed to derive predicted Zenith Wet Delays (ZWDs) for each station. The predicted ZWDs are subsequently incorporated into the real-time PPP as virtual observations, thereby enhancing the performance of the real-time PPP time transfer. One week of data from 20 globally distributed stations was used to form 19 time links. Results showed that the average root mean square error (RMSE) for the predicted ZWD amounts to 1.4 cm. For the traditional PPP strategy with ZWD estimation, the average convergence time of all links is 7.18 and 9.24 min for the static and kinematic modes, respectively. With the ZWD augmentation, they are shortened to 5.77 and 7.26 min, with improvements of 19.6% and 21.4%, respectively. In terms of the time link precision, the traditional and GFS ZWD-augmented methods yield 0.483 and 0.414 ns in the static mode, and 0.607 and 0.508 ns in the kinematic mode, with improvements of 14.3% and 16.3%, respectively. Regarding time link stability, improvements range from 10.0 to 20.6% in the static mode and from 9.7 to 21.4% in the kinematic mode when the averaging time is from 30 to 3600 s. These results clearly demonstrate that incorporating ZWD as external constraints can significantly enhance real-time PPP time transfer, particularly during the convergence period.

Characterizing the metabolomic fingerprint of fermented soymilk through the development of phage-resistant Lactiplantibacillus plantarum mutants - Yingtong Chen; Yan Lei; Mengjun Cui; Dongqing Zhang; Jinghai Yang; Xia Chen (International Journal of Food Microbiology, 2026)

Resilient bioconversion of nitrite-rich organic wastes by black soldier fly larvae: Detoxification mechanisms and microbiome-mediated nitrogen cycling - Chaowei Qin; Mengjun Long; Jiabao Chen; Dan Shao; Shanshan Zhao; Long Chen; Zhenyu Zhang; Lijun Duan; Huan He; Juan Cortes Ortiz; Hui Wei; Qing Li; et al. (International Biodeterioration & Biodegradation, 2026)

Hydration mechanism, mechanical properties and environmental performance of electrolytic manganese residue based total solid waste supersulfate cement - Dejun He; Junying Li; Guiji Tu; Mengjun Chen; Yunhui Han (Process Safety and Environmental Protection, 2026)

New Insights into the multifunctional mechanisms of polyaniline/Fe₃O₄-biochar in anaerobic co-digestion: Electron shuttling, microbial community succession, and metabolic regulation - Boyang Li; Sijia Chen; Jinzhi Zou; Jianwei Zhao; Jinxu Zhang; Mengjun Zeng; Yingjie Sun; Weidong Ye (Process Safety and Environmental Protection, 2026)

Structural performance of CFRP-wrapped corroded subsea pipelines subjected to settlement movement - Bangrui Xu; Jinghong Xue; Bohan Xia; Tong Han; Mengjun Chen (Ocean Engineering, 2026)

One-step transformation of hazardous WPCBs into 4N-grade copper via slurry electrolysis: Leveraging the Cu-NH3-Cl synergistic cycle for sustainability - Shuyuan Chen; Qian Liang; Mengjun Chen (Journal of Hazardous Materials, 2026)

In situ experimental study of the 10 Å phase in NaCl-H2O fluids: Implications for the deep water cycle - Mengjun Xiong; Zhi Zheng; Jiangzhi Chen; Xia Zhao; Shenghua Mei (Acta Geochimica, 2026)

Copper recovery from the smelting products of copper electroplating sludge by roasting and slurry electrolysis - Jinchuan Qin; Rong Wang; Yin Huang; Qian Liang; Jiancheng Shu; Mengjun Chen (Waste Management, 2026)

Study on the electrocatalytic reduction mechanism of PFOA degradation at gradient sulfur-doped copper sites - Hailong Wang; Ruijie Ge; Chenjian Ye; Jianzhong Zhu; Jue Liu; Liang Chen; Mengjun Xu; Jianbo Ma (Environmental Research, 2026)

Electrochemical oscillation on lead recovery from spent lead paste by suspension electrolysis - Xingyu Luo; Jiqin Wang; Dejun He; Yunhui Han; Xiangfei Zeng; Ling Hu; Qian Liang; Hao Li; Anlong Han; Jianchen Shu; Mengjun Chen (Journal of Environmental Chemical Engineering, 2026)

A pilot-scale certification for copper recovery from waste printed circuit boards by NH3-NH4Cl-CuSO4 slurry electrolysis: perspective but challenge - Qian Liang; Ling Hu; Xiangfei Zeng; Jinchuan Qin; Yunhui Han; Huimin Yang; Huan Li; Xingyu Luo; Shuyuan Chen; Shaoqin Chen; Jiqin Wang; Jiancheng Shu; et al. (Journal of Environmental Chemical Engineering, 2026)

Rational design of CRISPR–Cas12a crRNAs for enhanced allelic discrimination and low-abundance variant detection - Wei Wu; Yijie Gong; Mengjun Deng; Manlu Yang; Lifeng Wang; Yuanyuan Wang; Li Yang; Xueping Chen; Guoming Xie; Junjie Li (Chemical Engineering Journal, 2026)

Silicon accumulation in Dendrocalamus ronganensis leaves: Monthly variability and environmental sensitivity - Rencheng Li; Mengjun Hu; Xiaofang Chen; Jun Fan; Ying Zhang; Zongyu Xiao; Yuzhe Wu; Xiajuan Li (Plant and Soil, 2026)

Mechanism of efficient selective separation and purification of Cu, In, and Ga in the deep eutectic solvents system - Hang Zhao; Mengjun Chen; Yusheng Tang; Haile Yan; Feihua Yang; Xiaoguang Zhang (Journal of Cleaner Production, 2026)

Rapid grouting evaluation with magnetic detection: Methods and mechanisms - Botao Wang; Jiacheng Zhang; Luoluo Song; Zhiheng Wang; Rentai Liu; Xiuhao Li; Shihao Luo; Mengjun Chen; Jiwen Bai (Journal of Applied Geophysics, 2026)

Efficient conversion mechanism of calcium fluoride in fluoride-containing sludge by calcination - Hang Zhao; Mengjun Chen; Feihua Yang; Haile Yan; Xiaoguang Zhang; De’an Pan (ENGINEERING Environment, 2026)

Sensory-metabolomics insights into quality alteration of dried jujube (Ziziphus jujuba ‘Huizao’) fruit in prolonged storage - Ye Yuan; Lili Li; Jiamin Li; Xiaojuan Yang; Shoule Wang; Bingqi Shen; Chong Chen; Juan Jin; Lei Yang; Dingyu Fan; Mengjun Liu; Zhihui Zhao; et al. (Food Chemistry, 2026)

A novel method for desulfurization of electrolytic manganese residue using KHCO3: Mechanisms of sulfate transformation and heavy metal mineralization - Hongyuan Zhao; Jiancheng Shu; Fan Lin; Jing Wang; Jun Luo; Yong Yang; Mengjun Chen (Process Safety and Environmental Protection, 2025)

Sr(Ⅱ) and Cs(Ⅰ) adsorbed by graphene synthesized from spent lithium-ion batteries anode materials via novelly electrochemical exfoliation - Xingying Fan; Xiangfei Zeng; Yunhui Han; XingYu Luo; Huan Li; Xingyu Xiao; Jin Bai; Mengjun Chen (Journal of Environmental Radioactivity, 2025)

Synthesis of lithium-ion sieves based on electrolytic manganese anode slime: Characterization and its lithium adsorption performance - Jun Luo; Jiancheng Shu; Hongyuan Zhao; Jing Wang; Shaoqin Chen; Huimin Yang; Fan Lin; Sha Zhang; Mengjun Chen; Yong Yang (Chemical Engineering Journal, 2025)

The co-incorporation of rice straw and Chinese milk vetch enhances soil carbon retention by regulating the transformation of labile organic carbon fractions in paddy fields - Wangwang Zhang; Yuhong Wu; Fei Xu; Yuhang Qin; Hao Chen; Lv Wang; Mengjun Hu; Shuo Li (European Journal of Agronomy, 2025)

Sodium alginate/carboxymethyl chitosan/gelatin-naringenin pH-responsive hydrogel beads for oral delivery of traditional Chinese herbal medicines - Zixing Yan; Qingling Nie; Jiajia Liu; Jingxin Chen; Youmei Liu; Yudong Lu; Mengjun Xu; Zhenwen Lin (Carbohydrate Polymers, 2025)

Ultra-sensitive detection of complex SNVs via allele-specific dPCR enhanced by multi-strand displacement reaction - Mengjun Deng; Xueping Chen; Guoming Xie; Junjie Li (Chemical Engineering Journal, 2025)

Strengthening mechanism of water content reduction in electrolytic manganese residue by sodium oleate - Jing Wang; Zihan Li; Jiancheng Shu; Zongchen Wei; Shaoqin Chen; Hongyuan Zhao; Jun Luo; Huimin Yang; Yanyan You; Mengjun Chen; Yong Yang (Journal of Environmental Chemical Engineering, 2025)

Enhancing the separation of iron and manganese from high-iron rhodochrosite through medium-low temperature calcination and leaching - Jiaming Chen; Jiancheng Shu; Huimin Yang; Sha Zhang; Jun Luo; Jing Wang; Hongyuan Zhao; Zongchen Wei; Yong Yang; Zongyu Deng; Mengjun Chen (Process Safety and Environmental Protection, 2025)

In Situ experimental study of talc carbonation in C-O-H fluid: Implications for the deep carbon cycle - Mengjun Xiong; Zhi Zheng; Jiangzhi Chen; Xia Zhao; Shenghua Mei (Geochimica et Cosmochimica Acta, 2025)

Plant above-ground biomass drives the recovery of soil microbial communities in a subtropical-temperate transition zone following forest wildfire - Mengjun Hu; Jiayin Feng; Yu Shi; Pengshuai Shao; Zhijie Chen; Zhenxing Zhou; Jiali Wang (Applied Soil Ecology, 2025)

Electrochemical oscillation during copper recovery from waste printed circuit boards by slurry electrolysis: Generation mechanism and process characteristics - Jiqin Wang; Qian Liang; Xiangfei Zeng; Shuyuan Chen; Mengjun Chen (Journal of Environmental Management, 2025)

Jarosite residues recycling by slurry electrolysis: Iron recovery and detoxification in one step - Rong Wang; Mengjun Chen; Wei Fan; Xiangfei Zeng; Yunhui Han; Qian Liang; Rong Huang; Songshan Zhou; Jiancheng Shu (Process Safety and Environmental Protection, 2025)

Selective complex leaching of Cu, Zn, and Cd from recycled copper smelting fly ash using NH3-NH4Cl system and kinetic analysis - Fan Lin; Tianya Lei; Jiancheng Shu; Mengjun Chen; Jibamu Duo; Xiangfei Zeng; Yunhui Han; Shaoqin Chen; Jiaming Chen; Weiping Huang; Jun Luo (Process Safety and Environmental Protection, 2025)

Enhanced removal of Cr(VI) from aqueous solutions by an electric field and iron–manganese oxalate composites - Shushu Liao; Kaiyuan Liang; Jiancheng Shu; Yunhui Han; Jiaming Chen; Shaoqin Chen; Jun Luo; Shengjie Wang; Mengjun Chen; Hanke Wei; Zongyu Deng (Journal of Environmental Chemical Engineering, 2025)

Characterization and Correlation Analysis of Bacterial Composition and Physicochemical Quality in High- and Medium-Temperature Daqu from China’s Binzhou Region - Mengjun Cui; Wenchao Cai; Peirong Yu; Wei Chen; Chunhui Shan; Guo Zhuang; Yurong Wang (Current Microbiology, 2025)

Advances on jarosite residue detoxification and reutilization: a review - Mengjun Chen; Rong Wang; Wei Fan; Jiqin Wang; Xiangfei Zeng; Yunhui Han; Qian Liang; Rong Huang; Songshan Zhou; Jiancheng Shu (Environmental Science and Pollution Research, 2025)

Regulation of skin pigments in winter jujube fruit treated with elevated O2 - Dong Li; Wenxuan Li; Qingqing Wang; Yanpei Chen; Yanqun Xu; Xingtao Zhang; Zhihui Zhao; Mengjun Liu; Qinyang Cheng; Zisheng Luo (Postharvest Biology and Technology, 2024)

Fire alters soil bacterial and fungal communities and intensifies seasonal variation in subtropical forest ecosystem - Ziyue Shi; Yaru Chen; Aogui Li; Mengjun Hu; Weixing Liu (European Journal of Soil Biology, 2024)

Iron separation from iron-rich manganese ore leachate: Comprehensive optimization of operating parameters and economic viability - Zhisheng Zhao; Jiancheng Shu; Xiangfei Zeng; Mengjun Chen; Ling Hu; Zongyu Deng; Liang Ma; Shengjie Wang; Yong Yang; Hanke Wei (Chemosphere, 2024)

Torsional vibration analysis and fuzzy adaptive PID control optimization of underwater vector propulsion shaft systems - Zhengyu Chen; Yingchun Jia; Mengjun Wang; Shuaishuai Li; Songmei Li (Ocean Engineering, 2024)

A novel fluorescence immunoassay for the quantitative detection of florfenicol in animal-derived foods based on ZnCdSe/ZnS quantum dot labelled antibody - Cheng Xin; Jingming Zhou; Yumei Chen; Yankai Liu; Hongliang Liu; Chao Liang; Xifang Zhu; Ying Zhang; Zhuting Chen; Xueyuan Tang; Bingxue Zhang; Mengjun Lu; et al. (Food Chemistry, 2024)

Engineering PD-L1 targeted liposomal canagliflozin achieves multimodal synergistic cancer therapy - Simeng Wang; Mengjun Sui; Quan Chen; Jiahua Guo; Huini Yang; Ye Zhou; Meiju Ji; Yangyang Cheng; Peng Hou (Chemical Engineering Journal, 2024)

Decoding the biochemical dialogue: metabolomic insights into soybean defense strategies against diverse pathogens - Min Qiu; Mengjun Tian; Yaru Sun; Huaibo Li; Wenwen Huang; Haibing Ouyang; Shaoyan Lin; Chen Zhang; Ming Wang; Yuanchao Wang (Science China Life Sciences, 2024)

Analysis of binding and authentic virus-neutralizing activities of immune sera induced by various monkeypox virus antigens - Shuo Song; Zuning Ren; Jiayin Chen; Mengjun Li; Yushan Jiang; Yingxia Liu; Bao Zhang; Hongzhou Lu; Wei Zhao; Chenguang Shen; Yang Yang (Immunologic Research, 2024)

Taxonomic turnover dominates changes in soil microbial communities and functions in response to wildfire in subtropical forest - Ziyue Shi; Yaru Chen; Aogui Li; Chao Wang; Mengjun Hu; Weixing Liu (Applied Soil Ecology, 2024)

Nanocluster-agminated amorphous cobalt nanofilms for highly selective electroreduction of nitrate to ammonia - Minghang Jiang; Mengfei Zhu; Junjie Ding; Huaizhu Wang; Qianchuan Yu; Xi Chen; Yi He; Mengjun Wang; Xiaojun Luo; Caijun Wu; Liyun Zhang; Xinghui Yao; et al. (Journal of Hazardous Materials, 2024)

Cropland inundation mapping in a mountain dominated region based on multi-resolution remotely sensed imagery and active learning for semantic segmentation - Hao Jiang; Jianhui Xu; Xun Zhang; Xia Zhou; Yangxiaoyue Liu; Mengjun Ku; Kai Jia; Xuemei Dai; Yishan Sun; Shuisen Chen (Journal of Hydrology, 2024)

c-Jun targets miR-451a to regulate HQ-induced inhibition of erythroid differentiation via the BATF/SETD5/ARHGEF3 axis - Yanrong Lv; Xiaoju Ma; Qing Liu; Zihao Long; Shuangqi Li; Zhaoqing Tan; Dongsheng Wang; Xiumei Xing; Liping Chen; Wen Chen; Qing Wang; Qing Wei; et al. (Toxicology, 2024)

Electrolytic manganese residue pretreated by filter press-water washing and carbide slag: Manganese recycling, depth harmless and dispersion - Dejun He; Mengjun Chen; Hui Liu (Process Safety and Environmental Protection, 2024)

Electrochemical oscillation behaviors of gold during its recovery from waste printed circuit boards through slurry electrolysis - Jiqin Wang; Xiangfei Zeng; Shuyuan Chen; Qian Liang; Mengjun Chen (Process Safety and Environmental Protection, 2024)

Multiomics integrated with sensory evaluations to identify characteristic aromas and key genes in a novel brown navel orange (Citrus sinensis) - Zhehui Hu; Mengjun Chen; Kaijie Zhu; Yuan Liu; Huan Wen; Jiatao Kong; Minghua Chen; Lixin Cao; Junli Ye; Hongyan Zhang; Xiuxin Deng; Jiajing Chen; et al. (Food Chemistry, 2024)

Empirical analysis of lead neurotoxicity mode of action and its application in health risk assessment - Hehai Huang; Yanrong Lv; Qingfei Chen; Xiaowei Huang; Jingyao Qin; Yan Liu; Qilong Liao; Xiumei Xing; Liping Chen; Qing Liu; Shuangqi Li; Zihao Long; et al. (Environmental Research, 2024)

Preparation of anti-washout cement-stabilized marine soft clay for scouring protection of wind power pile foundations - Xiuhao Li; Zhijing Zhu; Rentai Liu; Chunyu Zhang; Qingsong Zhang; Shucai Li; Mengjun Chen (Marine Georesources & Geotechnology, 2024)

Unlocking the secrets of Qingzhuan tea: A comprehensive overview of processing, flavor characteristics, and health benefits - Panpan Liu; Lin Feng; Jia Chen; Shengpeng Wang; Xueping Wang; Yanna Han; Mengjun Ma; Zhonghua Liu; Pengcheng Zheng (Trends in Food Science & Technology, 2024)

8-OHdG mediates the association of co-exposure to fifty-five typical endocrine-disrupting chemicals with renal function: a cross-section investigation in Southern Chinese adults - Qingfei Chen; Qifei Deng; Qilong Liao; Yan Liu; Zhaorui Zhang; Dehua Wu; Yanrong Lv; Jingyao Qin; Qing Liu; Shuangqi Li; Zihao Long; Xiumei Xing; et al. (Environmental Science and Pollution Research, 2024)

Photoaged microplastics enhanced the antibiotic resistance dissemination in WWTPs by altering the adsorption behavior of antibiotic resistance plasmids - Qian Guo; Mengjun Wang; Siyuan Jin; Haohua Ni; Shuping Wang; Jie Chen; Wenlu Zhao; Zhiguo Fang; Zhiheng Li; Huijun Liu (Science of The Total Environment, 2024)

A novel method for efficiently recycling platinum group metals and copper by Co-smelting spent automobile catalysts with waste-printed circuit boards - Rong Huang; Songshan Zhou; Jiaming Chen; Xiangfei Zeng; Yunhui Han; Jinchuan Qin; Yao Huang; Fan Lin; Xi Yu; Shushu Liao; Zhiqiang Chen; Yubin Han; et al. (Journal of Cleaner Production, 2024)

The spatial transcriptomic landscape of human gingiva in health and periodontitis - Zongshan Shen; Ran Zhang; Yunjia Huang; Jiayao Chen; Mengjun Yu; Chunhua Li; Yong Zhang; Lingling Chen; Xin Huang; Jichen Yang; Zhengmei Lin; Songlin Wang; et al. (Science China Life Sciences, 2024)

Synergistic harmless treatment of phosphogypsum leachate wastewater with iron-rich electrolytic manganese residue and electric field - Jiancheng Shu; Junjie Zhao; Xiaoqin Wei; Mengjun Chen; Bing Li; Yushi Gao; Yong Yang; Zongyu Deng (Minerals Engineering, 2023)

Effective extraction of nickel and cobalt from sintered nickel alloy via reduction roasting and leaching - Yongwei Wang; Xuejie Chang; Mengjun Chen; Wenqing Qin; Junwei Han (Minerals Engineering, 2023)

Enhanced recovery of high purity Cu powder from reclaimed copper smelting fly ash by NH3·H2O–NH4Cl slurry electrolysis system - Jiaming Chen; Tianya Lei; Jiancheng Shu; Wenxing Cao; Xiangfei Zeng; Fan Lin; Shushu Liao; Mengjun Chen; Liang Wei; Weiping Huang (Journal of Cleaner Production, 2023)

Microbiota from healthy mice alleviates cognitive decline via reshaping the gut-brain metabolic axis in diabetic mice - Qihui Zhao; Junli Chen; Mengjun Wu; Xiaoli Yin; Qiaoying Jiang; Hongchang Gao; Hong Zheng (Chemico-Biological Interactions, 2023)

Treatment of Water Inrush in Mine Engineering Using a Superabsorbent Polymer: A Case Study of a Limestone Mine, Pingnan, China - Chenyang Ma; Yu’an Gong; Mengjun Chen; Rentai Liu; Jiwen Bai; Zhuo Zheng; Mengmeng Zhou (Mine Water and the Environment, 2023)

Chlorine and heavy metals removal from municipal solid waste incineration fly ash by electric field enhanced oxalic acid washing - Hang Zhao; Feihua Yang; Zhaojia Wang; YinMing Li; Jianping Guo; Sha Li; Jiancheng Shu; Mengjun Chen (Journal of Environmental Management, 2023)

Double-photoelectrode redox desalination of seawater - Xing Wang; Mengjun liang; Jiancong Zhang; Xuncai Chen; Mono Zaw; Than Zaw Oo; Nyein Wint Lwin; Su Htike Aung; Yuan Chen; Fuming Chen (Water Research, 2023)

Electrolyte circulation: Metal recovery from waste printed circuit boards of mobile phones by alkaline slurry electrolysis - Qian Liang; Jiqin Wang; Shuyuan Chen; Shaoqin Chen; Ling Hu; Jinchuan Qin; Yunhui Han; Xiangfei Zeng; Xiaogang Li; Qingbin Guo; Mengjun Chen; Jiancheng Shu (Journal of Cleaner Production, 2023)

Zinc efficiently extracted from zinc calcine by reduced wet grinding: ZnFe2O4 to ZnO and Fe3O4 - Shaoqin Chen; Xiangfei Zeng; Qian Liang; Ling Hu; Shuyuan Chen; Dejun He; Yunhui Han; Zhisheng Zhao; Rong Huang; Yin Huang; Songshan Zhou; Jiqin Wang; et al. (Journal of Cleaner Production, 2023)

Solid-liquid interface adsorption of antibiotic resistance plasmids induced by nanoplastics aggravates gene pollution in aquatic ecosystems - Zhiheng Li; Mengjun Wang; Hong Fang; Zhangchao Yao; Huijun Liu; Wenlu Zhao; Jie Chen (Environmental Pollution, 2023)

Bioremediation of quinclorac injury on tobacco by a rhizosphere bacterium - Linhan Li; Ting Zhou; Linyu Zhong; Qian Zhou; Gang Gu; Mengjun Hu; Fengping Chen; Sheng Lin (World Journal of Microbiology and Biotechnology, 2022)

Evaluation of a Superabsorbent Polymer for Plugging Karst Pipe Type Water Inrushes - Chenyang Ma; Shucai Li; Rentai Liu; Yan Pei; Chunyu Zhang; Yankai Liu; Fei Xu; Xiao Feng; Mengjun Chen (Mine Water and the Environment, 2022)

The characteristics and genome analysis of vB_ApiP_XC38, a novel phage infecting Acinetobacter pittii - Mengjun Cheng; Man Luo; Hengyu Xi; Yunze Zhao; Shuai Le; Li-Kuang Chen; Demeng Tan; Yuan Guan; Tianqi Wang; Wenyu Han; Nannan Wu; Tongyu Zhu; et al. (Virus Genes, 2020)

Sol-gel hydrothermal synthesis of nano crystalline silicotitanate and its strontium and cesium adsorption - Rong Wang; Zhenggang Luo; Qiuxia Tan; Rui Wang; Shuyuan Chen; Jiancheng Shu; Mengjun Chen; Zhengxue Xiao (Environmental Science and Pollution Research, 2020)

Effect of ionic liquid [MIm]HSO4 on WPCB metal-enriched scraps refined by slurry electrolysis - Yaping Qi; Xiaoxia Yi; Yugai Zhang; Fansong Meng; Jiancheng Shu; Furong Xiu; Zhi Sun; Shuhui Sun; Mengjun Chen (Environmental Science and Pollution Research, 2019)

Isolation and identification of a Bacillus subtilis HZ-72 exhibiting biocontrol activity against flax seedling blight - Taimeng Tan; Jiuxiang Zhu; Airong Shen; Jilie Li; Yongting Yu; Mengjun Zhang; Mengrui Zhao; Zhimin Li; Jia Chen; Chunsheng Gao; Yi Cheng; Litao Guo; et al. (European Journal of Plant Pathology, 2019)

Polychlorinated biphenyls and organochlorine pesticides in atmospheric particulate matter of Northern China: distribution, sources, and risk assessment - Shuangshuang Ding; Faqin Dong; Bin Wang; Shu Chen; Liufei Zhang; Mengjun Chen; Mei Gao; Ping He (Environmental Science and Pollution Research, 2015)

Physiological and antioxidant responses of Basella alba to NaCl or Na2SO4 stress - Jianfeng Ning; Shaoying Ai; Shaohai Yang; Lihua Cui; Yong Chen; Lili Sun; Ronghui Wang; Mengjun Li; Zhaobing Zeng (Acta Physiologiae Plantarum, 2015)

Complete genome sequence of a novel infectious bronchitis virus strain circulating in China with a distinct S gene - Sheng Zhou; Mengjun Tang; Yi Jiang; Xu Chen; Xinyue Shen; Jianmei Li; Yabin Dai; Jianmin Zou (Virus Genes, 2014)